2016
DOI: 10.1038/srep34188
|View full text |Cite
|
Sign up to set email alerts
|

CIBZ Regulates Mesodermal and Cardiac Differentiation of by Suppressing T and Mesp1 Expression in Mouse Embryonic Stem Cells

Abstract: The molecular mechanisms underlying mesodermal and cardiac specification from embryonic stem cells (ESCs) are not fully understood. Here, we showed that the BTB domain-containing zinc finger protein CIBZ is expressed in mouse ESCs but is dramatically downregulated during ESC differentiation. CIBZ deletion in ESCs induced specification toward mesoderm phenotypes and their differentiation into cardiomyocytes, whereas overexpression of CIBZ delayed these processes. During ESC differentiation, CIBZ loss-and-gain-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 53 publications
2
22
1
Order By: Relevance
“…Indeed, ZBTB38 has been shown to repress overall transcription by inhibiting expression of MCM10, a component of the pre-replication complex [20]. Additionally, ZBTB38 can, directly or indirectly, regulate cell cycle progression, cellular differentiation, and apoptosis [21][22][23][24][25]. In contrast to this speculation, we demonstrate that, despite high levels of expression in germinal center B lymphocytes and plasma cells, ZBTB38 deficiency does not impair primary or secondary antibody responses to T cell-dependent model immunogens.…”
Section: Introductioncontrasting
confidence: 58%
“…Indeed, ZBTB38 has been shown to repress overall transcription by inhibiting expression of MCM10, a component of the pre-replication complex [20]. Additionally, ZBTB38 can, directly or indirectly, regulate cell cycle progression, cellular differentiation, and apoptosis [21][22][23][24][25]. In contrast to this speculation, we demonstrate that, despite high levels of expression in germinal center B lymphocytes and plasma cells, ZBTB38 deficiency does not impair primary or secondary antibody responses to T cell-dependent model immunogens.…”
Section: Introductioncontrasting
confidence: 58%
“…In vitro, ZBTB38 has preferential affinity for two different sets of methylated consensus sequences, which it binds through two different sets of Zinc fingers ( 10–11 ). As ZBTB38 represses transcription ( 9 , 12 , 22 , 49 ), its role against oxidative stress could entail dampening the expression of methylated genes. Potential candidates include genes regulating the production of ROS by mitochondria, and their detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we hypothesized that DNMTi might have an effect on the transcription factors that bind methylated DNA, so we evaluated the impact of 5-azacytidine on the function and expression of the zinc finger and BTB domain containing protein ZBTB38, that binds to methyl-CpGs 26 28 . ZBTB38 is involved in various cellular functions, including the regulation of DNA replication, the control of gene expression and the regulation of cell proliferation and differentiation 26 , 29 32 . We observed that 5-azacytidine causes the down-regulation of ZBTB38 protein expression.…”
Section: Introductionmentioning
confidence: 99%